THE DEVELOPMENT OF ROLE PLAYING GAME (RPG) “IN MEINEM TRAUM” AS A LEARNING MEDIA FOR GERMAN READING SKILL IN ELEVENTH GRADE OF SMA - Rizka Zakiyya Mufida; Deddy Kurniawan (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2018)
This research and development aimed to develop Role-Playing Games (RPG) “in meinem Traum” which used as learning media of reading skill for eleventh grade students of senior high school. This research and development used the Richey’s, Klein’s, and Nelson’s development model type 1. The procedures are Analysis Phase, Design Phase, Development Phase, and A Try Out and Evaluation Phase. Based on the result of the analysis in the open questionnaire which had been filled by material and media experts, as well as the result of the analysis in the observation of the trial, it can be concluded that the RPG media “in meinem Traum” can be used as a learning media in reading skill for students of eleventh grade of senior high school.